Non-Operative Management of Acute Uncomplicated Appendicitis in Children - Nabibux Napar, Noor Ahmed Shaikh, Imamuddin Baloch, Azhar Ali Shah, Ishrat Mahtam, Inayatullah Memon, Nabibux Napar, Noor Ahmed Shaikh, Imamuddin Baloch, Azhar Ali Shah, Ishrat Mahtam, Inayatullah Memon (Journal of Rawalpindi Medical College, 2022)
Objective: To compare the efficacy of non-surgical conservative management with surgical management in cases of uncomplicated acute appendicitis in children. Study design: Prospective comparative study. Settings: Pediatric surgery Department, –removed for blind review—- Study duration: 1st February 2020 to 31st May 2021. Methodology: Ninety patients of either gender with age range from 5-12 years, diagnosed as uncomplicated acute appendicitis, were divided in two groups. Group C patients were managed conservatively with antibiotics (ceftriaxone 100 mg/kg/day, amikacin 10mg/kg/day and metronidazole 22.5 mg/kg/day) and maintenance fluids were started. Patients were observed for improvement or any signs of deterioration. Those who deteriorated within 24 hours were management with surgical management immediately. Follow ups were carried out after discharge at 7th day, 1 month and six months. Patients reporting with recurrence of symptoms were managed with appendicectomy. Group S patients were managed with appendicectomy with open technique. Patients were observed for post-operative complications. Results: Demographic data of both groups was comparable. In group C, 34 (75.56%) patients were successfully treated with conservative management, whereas in group S, 39 (86.67%) were successfully treated with surgical management. The difference was insignificant with a p-value of 0.114. In group C, 5 (11.11%) patients did not respond to conservative management and they were managed with appendicectomy and recurrence of symptoms was seen in 6 (13.33%) patients in group C, they were also managed with appendicectomy. In group S, 6 (13.33%) patients suffered post-operative complications. Mean length of stay in hospital was 4.31±1.20 and 4.09±1.12 days in group C and S respectively. This difference was statistically insignificant with a p-value of 0.368. Conclusion: It is concluded in our study that uncomplicated acute appendicitis in children can be successfully managed with non-surgical conservative management. Keywords: Acute appendicitis, Appendicectomy, Conservative management, Non-surgical management, Pediatric surgery, Uncomplicated acute appendicitis.